Polymorphism and association analysis of a drought-resistant gene TaLTP-s in wheat - Qian LI; Jing-yi WANG; Nadia Khan; Xiao-ping CHANG; Hui-min LIU; Rui-lian JING (Journal of Integrative Agriculture, 2016)
Lipid transfer protein (LTP) is a kind of small molecular protein, which is named for its ability to transfer lipid between cell membranes. It has been proved that the protein is involved in the responding to abiotic stresses. In this study, TaLTP-s, a genomic sequence of TaLTP was isolated from A genome of wheat (Triticum aestivum L). Sequencing analysis exhibited that there was no diversity in the coding region of TaLTP-s, but seven single nucleotide polymorphisms (SNPs) and 1 bp insertion/deletion (InDel) were detected in the promoter regions of different wheat accessions. Nucleotide diversity (π) in the region was 0.00033, and linkage disequilibrium (LD) extended over almost the entire TaLTP-s region in wheat. The dCAPS markers based on sequence variations in the promoter regions (SNP-207 and SNP-1696) were developed, and three haplotypes were identified based on those markers. Association analysis between the haplotypes and agronomic traits of natural population consisted of 262 accessions showed that three haplotypes of TaLTP-s were significantly associated with plant height (PH). Among the three haplotypes, HapIII is considered as the superior haplotype for increasing plant height in the drought stress environments. The G variance at the position of 207 bp could be a superior allele that significantly increased number of spikes per plant (NSP). The functional marker of TaLTP-s provide a tool for marker-assisted selection regarding to plant height and number of spikelet per plant in wheat.